2009
DOI: 10.1007/s00415-009-5387-9
|View full text |Cite
|
Sign up to set email alerts
|

How predictive is the MMSE for cognitive performance after stroke?

Abstract: Cognitive deficits are commonly observed in stroke patients. Neuropsychological testing is time-consuming and not easy to administer after hospital discharge. Standardised screening measures are desirable. The Mini-Mental State Examination (MMSE) is the test most widely applied to screen for cognitive deficits. Despite its broad use, its predictive characteristics after stroke have not been exhaustively investigated. The aim of this study was to determine whether the MMSE is able to adequately screen for cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(98 citation statements)
references
References 32 publications
(48 reference statements)
4
84
0
8
Order By: Relevance
“…It has been shown that MMSE or Abbreviated Mental Test are insensitive to mild cognitive impairment and executive function. 19,24,25 Although these are limitations in detecting mild cases, this study has shown high prevalence of cognitive impairments. Similar large long-term studies of poststroke cognitive function using sensitive tools to detect all cases, including mild cognitive impairments, will be of benefit to reconfirm the burden of this condition.…”
Section: Strokementioning
confidence: 73%
See 1 more Smart Citation
“…It has been shown that MMSE or Abbreviated Mental Test are insensitive to mild cognitive impairment and executive function. 19,24,25 Although these are limitations in detecting mild cases, this study has shown high prevalence of cognitive impairments. Similar large long-term studies of poststroke cognitive function using sensitive tools to detect all cases, including mild cognitive impairments, will be of benefit to reconfirm the burden of this condition.…”
Section: Strokementioning
confidence: 73%
“…[19][20][21] It not only provides population estimates, to our knowledge for the first time, on the longer term cognitive outcomes in a diverse innercity population, but it also highlights the long-term impacts of stroke in subgroups of the population and illustrates the risk of cognitive impairment long term. It is rare that population-based studies estimate this range of outcomes in such a prospective …”
Section: Discussionmentioning
confidence: 99%
“…The subjects had a score below the 2 nd percentile of the K-MMSE score of the norm group were defined as VaD, and between the 2 nd and 10 th percentile were VCIND. 7,[14][15][16][17] Statistical Analysis…”
Section: -13mentioning
confidence: 99%
“…Unfortunately, 5 studies did not sufficiently report this information, 16,18,20,23,24 and 3 reported the mean time interval between assessments as >10 days. 11,15,25 Only 6 studies stratified sensitivity or specificity results according to demographic or stroke variables. 20,22,23,[25][26][27] …”
Section: Sensitivity and Specificity Methodologymentioning
confidence: 99%
“…11,15,25 Only 6 studies stratified sensitivity or specificity results according to demographic or stroke variables. 20,22,23,[25][26][27] …”
Section: Sensitivity and Specificity Methodologymentioning
confidence: 99%